Progress in preventing injuries: from international collaboration to local implementation. (1st March 2011) - Sethi, D; Mitis, F; Racioppi, F
Abstract : Introduction: Injuries and violence are the third leading cause of death in WHO European Region and pose a threat to economic and social development. Aim and methods: The results of a 3-year collaborative project between WHO and the European Commission on progress achieved by Member States in implementing resolution EUR/RC55/R9 and the European Council Recommendation on the prevention of injuries are presented. A web-based database of country profiles was developed using a questionnaire survey completed by health ministry focal persons for injury and violence prevention. Information was provided on progress in delivering on key items of resolution EUR/RC55/R9 and on the implementation of 99 selected evidence-based programmes to prevent unintentional injury and violence and on the cross-cutting risk factors of alcohol and socioeconomic inequalities. Results: There were responses from 47 of the 51 Member States with focal persons. Good progress is taking place, and resolution EUR/RC55/R9 has catalysed change in 75% of respondent countries. Development of national policies for individual types of injury and violence varied from 95% for road safety to 40% for preventing drowning. Implementation of evidence-based programmes for preventing all types of injury and violence varied in countries, and the median score was 73% for all these together. Conclusions: This project reports that the health sector needs to commit more to the widespread implementation of effective programmes both in number and coverage, and to engage with other stakeholders in a multisectoral response to prevent injuries and violence.